Mapping Manuscript Migrations Knowledge Graph - Burrows, T; Hyvönen, E; Ransom, L; Wijsman, H; Page, K (University of Oxford, 2020)
The Mapping Manuscript Migrations (MMM) project transformed three separate datasets into a unified knowledge graph. The source databases include: * Schoenberg Database of Manuscripts from the Schoenberg Institute for Manuscript Studies; * Bibale database from the Institute for Research and History of Texts,;and, * Medieval Manuscripts Catalogue from the Bodleian Libraries.